EVALUATION OF THE ANTIGENICITY AND IMMUNOGENICITY OF Eimeria tenella BY REPRODUCTIVE INDEX AND HISTOPATHOLOGICAL CHANGES OF CECAL COCCIDIOSIS VIRULENT LIVE VACCINE IN BROILER CHICKENS - Suprihati, Endang; Yunus, Muchammad (African Journal of Infectious Diseases (AJID), 2018)
Background: The development of vaccine to control coccidiosis caused by Eimeria tenella (E. tenella) in chickens is intensifying because of the increasing threat of drug resistance to anticoccidial agents. It is important, therefore, to develop a reliable standard method for the assessment of vaccine afficacy particularly antigenicity and immunogenicity become crucial. Evaluation of E. tenella antigenicity and immunogenicity to some low doses can be reflected by reproductive index and histopathological changes.Materials and Methods: The complete random design of research was used in this study. Sixty of two weeks old broilers were divided into four groups and each group composed 15 replications. The group 1 was chicken group without virulent E. tenella oocyst inoculation. The group 2, 3 and group 4 were chicken group inoculated with virulent E. tenella oocyst at doses of 1.0 x 102, 2.0 x 102, 3.0 x 102, respectively. Then all chicken groups were challenged with E. tenella oocyst at doses of 1.0 x 103. Observation of research that represented antigenicity and immunogenicity was clinical sign, reproductive index, histopathological changes.Results: On virulent E. tenella inoculation step, some clinical signs such as appetite, weakness, and diarrhea were very slight on all chicken groups. While on challenge test step, there were no clinical signs of all chicken groups except the group 1. For the reproductive index of virulent E. tenella inoculation step, there were no significantly differences in all chicken groups except the group 1. As reproductive index, the same result pattern was seen for histopathological changes.Conclusion: The low number virulent E. tenella had low reproductive index and few histopathological changes effect that represents a promising strategy to prevent cecal coccidiosis in chickens.